Therapeutic Suppression of mTOR (Mammalian Target of Rapamycin) Signaling Prevents and Reverses Salt-Induced Hypertension and Kidney Injury in Dahl Salt-Sensitive Rats. Issue 3 (March 2019) - Kumar, Vikash; Evans, Louise C.; Kurth, Theresa; Yang, Chun; Wollner, Clayton; Nasci, Victoria; Zheleznova, Nadezhda N.; Bukowy, John; Dayton, Alex; Cowley, Allen W.
Abstract : mTOR (mammalian target of rapamycin) signaling has emerged as a key regulator in a wide range of cellular processes ranging from cell proliferation, immune responses, and electrolyte homeostasis. mTOR consists of 2 distinct protein complexes, mTORC1 (mTOR complex 1) and mTORC2 (mTOR complex 2) with distinct downstream signaling events. mTORC1 has been implicated in pathological conditions, such as cancer and type 2 diabetes mellitus in humans, and inhibition of this pathway with rapamycin has been shown to attenuate salt-induced hypertension in Dahl salt-sensitive rats. Several studies have found that the mTORC2 pathway is involved in the regulation of renal tubular sodium and potassium transport, but its role in hypertension has remained largely unexplored. In the present study, we, therefore, determined the effect of mTORC2 inhibition with compound PP242 on salt-induced hypertension and renal injury in salt-sensitive rats. We found that PP242 not only completely prevented but also reversed salt-induced hypertension and kidney injury in salt-sensitive rats. PP242 exhibited potent natriuretic actions, and chronic administration tended to produce a negative Na + balance even during high-salt feeding. The results indicate that mTORC2 and the related downstream associated pathways play an important role in regulation of sodium balance and arterial pressure regulation in salt-sensitive rats. Therapeutic suppression of the mTORC2 pathway represents a novel pathway for the potential treatment of hypertension. Abstract : Supplemental Digital Content is available in the text.